Analysis of amino acids in cell culture supernatant using capillary electrophoresis with contactless conductivity detection. Issue 19 (6th August 2021) - Mikkonen, Saara; Emmer, Åsa
Abstract: CE‐C 4 D methods for the analysis of amino acids (AAs) are presented. Combining the results from two methods with acetic acid and cyclodextrin‐based BGEs, 20 proteinogenic AAs could be analyzed using CE. CE‐C 4 D was also, for the first time, applied to analyze free AAs in samples of mammalian cell culture supernatant. After dilution as only sample preparation, combining the results of the two CE methods allowed monitoring the concentration changes of 17 AAs in samples taken during the cultivation of CHO cells.